MENCARI ALTERNATIF METODE IDENTIFIKASI KETERKAITAN STRUKTUR PASAR, EFISIENSI DAN PROFITABILITAS, DENGAN ANALISIS DINAMIK PANEL DATA - Jumono, Sapto; Fathmala, Chajar Matari (Lembaga Penerbitan Unversitas Esa Unggul, 2017)
This study aims to identify the market structure of the Indonesian banking industry. Particularly, this research tend to find out whether Indonesian banking adopts SCP hypothesis (Structure-Conduct Performance), RMP hypothesis (Relative Market Power), RES hypothesis (Relative Efficient Structure), SES (scale efficiency structure) hypothesis, or QL (Quiet Life) hypothesis. This research uses annual data of 10 largest commercial banks in Indonesia during 2009 to 2014 and using data panel regression analysis. The result shows that SCP hypothesis and RMP hypothesis are valid in Indonesian banking, while the RES hypothesis, SES hypothesis, and QL hypothesis are not valid.Â Keywords: Bank, Market structure, efficiency and profitability